Effect of Glycyrrhiza glabra L. on Broiler Growth Performance, Slaughter and Carcass Characteristics, Blood biochemistry, and Hematological Parameters: A Systematic Review - Esen Selim; Prete Andrea; Centoducati Gerardo; Lackner Maximilian; Palangi Valiollah; Tölü Cemil (The EuroBiotech Journal)
In this systematic review, 79 research articles focusing on the impact of Glycyrrhiza glabra L. (licorice) supplementation in broilers were meticulously examined, assessing growth performance, slaughter and carcass traits, and blood parameters. Out of these, 12 studies met the predefined criteria. Licorice supplementation, particularly in the absence of specific dietary constraints, signifi-cantly improved feed consumption, body weight gain, and feed conversion efficiency in broilers. The addition of licorice influ-enced slaughter and carcass traits, increasing the dressing percentage, although results varied based on dosage and form of supplementation. Effects on abdominal fat and spleen weights were inconsistent, while liver, heart, and gizzard weights gen-erally increased. Licorice supplementation affected blood biochemistry, showing varied impacts on markers like glucose, cho-lesterol, and triglycerides. Notably, licorice exhibited potential antioxidant properties by reducing malondialdehyde levels, in-dicating decreased oxidative stress. The review highlighted diverse outcomes across growth performance, slaughter traits, car-cass parameters, and blood biochemistry due to licorice supplementation. Variability in dosage, form, and administration methods underscored the need for standardized protocols. Future research should concentrate on uncovering underlying mechanisms, expanding geographical diversity, and exploring interactions with other feed additives, especially in antibiotic-free diets. Despite its promise, further investigation is necessary to optimize licorice’s role in poultry production.